2019
DOI: 10.33506/jq.v8i1.469
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Students’ Oral Communication By Using Communicative Language Teaching (CLT)

Abstract: This article aims at providing students’ oral communication in speaking class. There were two specific purposes to gain the data namely to find out the effects of Communicative Language Teaching (CLT) in teaching oral communication especially in speaking ability and to disclose the responses of students in the learning process by using Communicative Language Teaching (CLT). In order to obtain the comprehensive data, the writers used performance test and questionnaire with 32 respondents on speaking class. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…According to the traditional teaching method, students almost only listen to the teacher's lectures and follow the model, thus not developing students' creativity and thinking, leading to completely passive learners. Working in pairs, in small and large groups in context gives students authentic opportunities to learn English speaking effectively (Wael et al, 2019). Besides that, interviews play an important role in enhancing students' fluency; problem-solving activities which relate to types of topics and tasks (AL-Garni và Almuhammadi 2019).…”
Section: Clt Strategies To Improve English Speaking Skills Classroom ...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the traditional teaching method, students almost only listen to the teacher's lectures and follow the model, thus not developing students' creativity and thinking, leading to completely passive learners. Working in pairs, in small and large groups in context gives students authentic opportunities to learn English speaking effectively (Wael et al, 2019). Besides that, interviews play an important role in enhancing students' fluency; problem-solving activities which relate to types of topics and tasks (AL-Garni và Almuhammadi 2019).…”
Section: Clt Strategies To Improve English Speaking Skills Classroom ...mentioning
confidence: 99%
“…Otherwise, (Toro et al, 2018;Chang & S. Goswami, 2011;Akhter & Ashikuzzaman, 2019) supported the view that the use of teaching materials is suitable to the culture, level, and characteristics of learners, etc., contributes positively to the direction of communicative teaching. However, the other group (Lom, 2012;Farooq, 2015;(Wael et al, 2019); AL-Garni & Almuhammadi, 2019) believed that organizing many interactive activities in the classroom helps students enjoy learning English and developing their communication skills.…”
Section: Research Gapsmentioning
confidence: 99%
“…Out of the four English skills, speaking is considered to be one of the most important components for learning English as a successful communicative language. Wael et al, (2019) found that oral communication skills were effective in improving students' confidence and increasing their ability to communicate in a foreign language. Therefore, to achieve effective communication, students need to practice and develop a deep understanding of how to use English orally (Wael et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…to foster effective communication. Many researchers state the effectiveness of CLT in improving students' speaking skills (Anggraini, 2018;Toro et al, 2019; AL-Garni & Almuhammadi, 2019; Wael et al, 2019). However, its implementation in East Asian schools has been a concern raised by Littlewood (2006).…”
Section: Introductionmentioning
confidence: 99%